The Effect of Compression on the Void Coalescence under Strong Dynamic Loading. (28th February 2022) - Tu, Ruichen; Wei, Ning; Pei, Yongmao; Liu, Yan; Zhang, Fengguo; Zhang, Dongsheng
Abstract : The void coalescence under strong dynamic loading is a significant spallation process for ductile metals. Since the spallation is basically dominated by tension waves, most void coalescence studies have focused on the tension effect. However, it is known that in spallation, the material initially undergoes a strong compression wave, and then an irreversible deformation is produced by the compression wave inside the material. Therefore, in this paper, the effect of compression on the void coalescence is investigated using the molecular dynamics (MD) simulation. It was found that as the compressive strain increases, the yield strength decreases first and then increases. The results showed that due to the Bauschinger effect (BE), the yield strength decreases by 19.43% from 5.66 GPa without compressive loading to 4.56 GPa when the compressive strain is −7.5%, after which the yield strength increases. The voids do not coalesce when the compressive strain is −8%. In addition, it was found that during the compressive phase, the void surfaces would generate dislocations, which could obstruct the void coalescence in the tensile phase. Furthermore, under compressive loading, the temperature effect on the void coalescence was studied, and it was found that lower temperatures could suppress the void coalescence.